Water supply and sanitation services sector in Nigeria: The policy trend and practice constraints - Emmanuel M. Akpabio (University of Bonn, Center for Development Research (ZEF), 2012)
Water supply and sanitation provision has been at the core of international attention reflected in various international directives and declarations over the past three decades. How are such international priorities domesticated in the national and local policy agenda? This paper specifically assesses the Nigerian policy trend and practices in relation to water supply and sanitation coverage over the past ten decades. The review observed that the Nigerian water and sanitation policy environment is characterized by: a) too many short-lived policies without corresponding action; b) excessive and opportunistic use of some international policy instruments; c) very many agencies with none effectively in charge; d) unrealistic assumptions of situations and; e) poor implementation practices. Although this trend of observation seems a general problem in developing countries, the paper argues that the Nigerian case looks exceptional, to a large extent, given the peculiarities of ethnic politics, long years of military rule which undermined the evolution and development of necessary institutions in the water and sanitation sector, official corruption, among several other factors. These factors and others contribute to making public water supply and sanitation services inaccessible to the poor. Given the nature of observations, the review concludes with some necessary recommendations.
Keywords: 330; Water supply and Sanitation provision; Policy Practices; Implementation; Nigeria